2016
DOI: 10.1111/1462-2920.13584
|View full text |Cite
|
Sign up to set email alerts
|

Habitat and taxon as driving forces of carbohydrate catabolism in marine heterotrophic bacteria: example of the model algae‐associated bacterium Zobellia galactanivorans DsijT

Abstract: The marine flavobacterium Zobellia galactanivorans Dsij was isolated from a red alga and by now constitutes a model for studying algal polysaccharide bioconversions. We present an in-depth analysis of its complete genome and link it to physiological traits. Z. galactanivorans exhibited the highest gene numbers for glycoside hydrolases, polysaccharide lyases and carbohydrate esterases and the second highest sulfatase gene number in a comparison to 125 other marine heterotrophic bacteria (MHB) genomes. Its genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
130
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 103 publications
(137 citation statements)
references
References 112 publications
(157 reference statements)
7
130
0
Order By: Relevance
“…Examination of the genomic context of alyA1, its absence from the vast majority of Flavobacteriaceae possessing alginolytic PULs, and the phylogenies of homologs from distantly related bacteria suggested that alyA1 was recently acquired via HGT from marine Actinobacteria. Although Actinobacteria are not generally considered as major marine macroalgal polysaccharide degraders, a recent census of GHs and PLs in 126 genomes of marine heterotrophic bacteria (Barbeyron et al, 2016) showed that on average, marine actinobacterial genomes encoded 47 such enzymes (4 genomes available), which is comparable to the average 51 found in marine Bacteroidetes (21 genomes available). Therefore, the role of marine Actinobacteria in polysaccharide turnover may previously have been underestimated.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Examination of the genomic context of alyA1, its absence from the vast majority of Flavobacteriaceae possessing alginolytic PULs, and the phylogenies of homologs from distantly related bacteria suggested that alyA1 was recently acquired via HGT from marine Actinobacteria. Although Actinobacteria are not generally considered as major marine macroalgal polysaccharide degraders, a recent census of GHs and PLs in 126 genomes of marine heterotrophic bacteria (Barbeyron et al, 2016) showed that on average, marine actinobacterial genomes encoded 47 such enzymes (4 genomes available), which is comparable to the average 51 found in marine Bacteroidetes (21 genomes available). Therefore, the role of marine Actinobacteria in polysaccharide turnover may previously have been underestimated.…”
Section: Discussionmentioning
confidence: 97%
“…Zobellia strains are marine Bacteroidetes commonly associated with red, brown and green algae and are considered a normal component of the microbiota of healthy macroalgae (Hollants et al, 2013;Martin et al, 2015;Marzinelli et al, 2015). Zobellia galactanivorans was originally isolated from the red alga Delesseria sanguinea (Barbeyron et al, 2001) and exhibits impressive abilities to digest diverse algal polysaccharides (Barbeyron et al, 2016). Analysis of the Z. galactanivorans genome revealed 141 glycoside hydrolases (GHs), 15 polysaccharide lyases (PLs), 18 carbohydrate esterases and 72 sulfatases.…”
Section: Introductionmentioning
confidence: 99%
“…The complexity of PULs often scales with that of their cognate substrates ( Fig. 1) (52,53) and may include ancillary enzymes such as proteases (54), sulfatases (55,56), and phosphatases (57). These elegant systems constitute the major nutrient acquisition strategy deployed by Bacteroidetes bacteria and thus are intrinsically linked to the colonization of nutritional niches and the establishment of microbial ecosystems.…”
Section: Bacteroidetes and The Pul Paradigmmentioning
confidence: 99%
“…For example, PULs from Zobellia galactanivorans (55), Formosa agariphila (56), and Gramella forsetii (101) contain CAZyme portfolios tuned to the unique monosaccharide residues of algal polysaccharides and, not surprisingly, are also enriched in sulfatases (see also SulfAtlas, a new sulfatase classification database from the Marine Glycobiology and ABiMS teams at the Station Biologique de Roscoff [102; http://abims.sb-roscoff.fr/sulfatlas/]).…”
Section: Pulomicsmentioning
confidence: 99%
“…The marine bacterium Zobellia galactanivorans is a model organism for the increasingly recognized microbial conversion of algal biomass . The genome of Z. galactanivorans encodes four GH16 β‐agarases (EC 3.2.1.81), AgaA, AgaB, AgaC, and AgaD, which cleave internal β‐1,4‐galactosidic linkages in agarose producing agaro‐oligosaccharides (Figure ) .…”
Section: Introductionmentioning
confidence: 99%